Comparison of Hemoglobin A1c Results measured by three different Assay Methods in relation with Age and Hemoglobin Impacts - Najat M. H. Mohammed; Eman Ahamed Almaky (African Journal of Advanced Pure and Applied Sciences, 2025)
Hemoglobin A1c is a reliable index of glycemic control reflecting the mean blood glucose levels over the past three months and provides a sensitive predictor of developing risk of diabetes related complications. However, the accuracy of HbA1c measuring methods can be adversely affected by various assay techniques. This study is aimed to compare HbA1c results by three various assay methods in the group of medical laboratories in EL-Bieda City. EDTA blood collected from 36 diabetic patients were used to measure HbA1c by using three different assays including immunoassay technique, Boronate affinity and high-performance liquid chromatography at three medical centers; in EL-Bieda medical center, Ajabal-ALkdar diabetic and AL-Burj medical centers respectively. Hematology analyzer was used for complete blood picture (Hb, WBC and PLTs). Plasma was separated from so¬dium fluoride tubes for measuring fasting blood glucose levels (FBG). All data gathered were analyzed by R software version 3 using Correlation test, T-test and expressed as mean, median, minimum and maximum with p value is significant if less than 0.05. Results showed that there was no significant difference in glycated hemoglobin (HBA1c) measured by three protocols as p value is larger than 0.05 (p value =0.41), as well as Persons coefficient of correlation revealed that HbA1c and Hemoglobin (Hb) are not significantly correlated since the p-value is larger than the significance level alpha. (R= 0.083, p=0.41). A significant correlation was found between HbA1c and age (R= 0.2 and p-value =0.05). Additionally, the results demonstrated positive correlation between fasting blood glucose levels (FBG) and HbA1c with a p-value of 1.8e-09 (R=0.55), which is less than the significance level alpha. It can be concluded that with using various operators principles for estimating HbA1c, there was no obvious variation between the results obtained indicating the acceptable accuracy of analytical performance.